(untitled) (International relations and international law Journal, 2016)
The state of GDP in the Kazakhstan’s economy is considered in the article. The advantages and disadvantages of modern methods of calculating GDP are reviewed. Gross Domestic Product (GDP, GNP, Gross National Product) is a market value of all eventual commodities and services (id est intended for a direct consumption), produced for investigated period in all industries of economy on territory of the state for a consumption, export and accumulation, without depending on national belonging of the used factors of production. Often GDP is used as a synonym to the word « economy», because reflects the scales of economic activity in a country. For an analysis and comparison the real GDP from that influence of change of standard of prices is excluded in a country is used. However, sometimes at strong fluctuations in exchange a government and ЦБ are oriented on the nominal increase of Gross Internal Product, aspiring to weakening of course for maintenance of height in nominal expression, that also renders a stimulant effect on a production and consumption. In spite of the fact that GDP is one of key for understanding of macroeconomic situation in a country, directly the publication of this index has a limit influence on a market. The analysis showed the dynamics of GDP in the Republic of Kazakhstan for the period of ten years. The causes of reduction are identified in GDP growth. Based on these data, taken into account the new solutions for the economic growth of Kazakhstan’s economy.